Achieving core maintenance quality competencies through profiling: theorisation and ESS development. (20th November 2006) - Elangovan, K.; Selladurai, V.; Devadasan, S.R.
In the contemporary literature, maintenance quality is considered as one of the world-class manufacturing strategies, yet the profiling and positioning of organisations towards maintenance quality strategies is seldom addressed. Research to overcome this situation is reported in this paper. Findings derived from the literature on profiling and positioning of management strategies were used to design a roadmap for developing maintenance quality profiles. Given the vital role of the CEO in developing successful maintenance quality profiles, a module of Executive Support System (ESS) named ESSMAQ was developed. Initial feedback on ESSMAQ, obtained from the executives of two companies, was favourable.